Die hieratische Stele MAA 1939.552 aus Amara West – ein neuer Feldzug gegen die Philister - Popko, Lutz (Zeitschrift für ägyptische Sprache und Altertumskunde, 2016)
Edition of stela MAA 1939.552, which was discovered in Amara West in 1938, but which was never properly published. The text is of a military nature and records a yet unknown land battle against the Philistines in the year 3 of a king whose name is lost. Whereas the stela was previously assigned to Ramses IV, a dating into the reign of Ramses III is proposed, thereby predating the beginning of the conflict with this group of the Sea Peoples by five years. Moreover, the text is partially incised in hieratic, which is unusual for royal war reports, and thus it provides further, exceptional evidence for lapidary hieratic.